High nitrogen composition–induced low interfacial roughness of GaAs0.978N0.022/GaAs multiple quantum wells grown through solid-source molecular beam epitaxy. (April 2017) - Biswas, Mahitosh; Tongbram, Binita; Shinde, Nilesh; Makkar, Roshan Lal; Bhatnagar, Anuj; Chakrabarti, Subhananda
Graphical abstract: Highlights: Five-period GaAsN/GaAs multiple quantum wells grown by varying nitrogen pressure. Low interface roughness because of nitrogen's occupancy at arsenic lattice sites. A relatively sharp interface-induced high intensity in photoluminescence spectra. 100-fold improvement in optical properties after rapid thermal annealing at 700 °C. Abstract: GaAs1−x Nx /GaAs multiple quantum wells (MQWs) were grown on GaAs(001) substrates through solid-source molecular beam epitaxy under various nitrogen background pressures (NBPs), and the crystal quality at the interface of GaAs1−x Nx and GaAs was investigated. X-ray diffraction and electron microscopy confirmed the low interface roughness of MQWs grown at a NBP of 5 × 10 −6  Torr. Surface morphology measurements revealed a smooth surface without whisker-like defect structures. The fabricated MQWs exhibited high photoluminescence intensity because of the reduction in surface recombination with high nitrogen incorporation. Raman spectroscopy confirmed the presence of N-like local vibrational mode, and this was attributed to the presence of phase separation in GaAsN alloys. Rapid thermal annealing improved photoluminescence intensity by 100-fold and substantially reduced full width at half maximum because of MQW homogenization. These results evidence the favorable crystal interface of GaAs0.978 N0.022 alloys. Hence, GaAs0.978 N0.022 /GaAs MQWs grown under high pressure might be useful in fabricating optoelectronic devices.